Urokinase plasminogen activator, uPAR, MMP-2, and MMP-9 in the C6-glioblastoma rat model - Schuler, Patrick; Bendszus, Martin; Kuehnel, Siglinde; Wagner, Sven; Hoffmann, Thomas K.; Goldbrunner, Roland; Vince, Giles Hamilton (In vivo, 2012)
Background: In glioblastoma multiforme (GBM), the serine protease urokinase plasminogen activator (uPA), and matrix metalloproteases (MMP-2 / MMP-9) contribute to its invasive growth pattern, which is the major obstacle to successful surgical treatment. Materials and Methods: The expression of uPA was determined in monolayers and spheroids of the rodent GBM cell line C6 by immunohistochemistry and polymerase chain reaction (PCR). The longitudinal expression of proteases was studied in orthotopically implanted spheroids by semi-quantitative immunohistochemistry (IHC) in Sprague Dawley rats (n=40). The tumor volume was monitored by magnetic resonance imaging (MRI). Results: In vitro, the GBM cell line C6 expresses high levels of uPA. In vivo, a continuous increase of uPA, uPA-receptor (uPAR), MMP-2, and MMP-9 expression was found in the infiltration zone. uPA was located exclusively in the infiltration zone and in the vascular basal layers. The mean tumor volume 23 days after implantation was 3.2 mm3. Conclusion: uPA, uPAR, MMP-2 and MMP-9 play an important role in GBM growth. Blockade of uPA and interruption of the proteolytic cascade could become a useful tool in the therapy of GBM.